2001
DOI: 10.1007/bf02702216
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of source parameters of Chamoli Earthquake, India

Abstract: In this paper the source parameters of this event calculated from the Strong Motion Data are presented. The seismic moment for this event has been found to be of the order of 10 25 dyne.cm and the moment magnitude has been calculated in the range of 6.53-6.69 at different stations. The stress drop and source radius for the earthquake are also calculated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 8 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…The determined values of the stress drop are listed in Table 3, they are in the range from 1.17 to 778.3 bar. Pandey et al, 2001 have been reported such high values of the stress drop for Chamoli earthquake, India.…”
Section: Stress Drop (Dd)mentioning
confidence: 92%
See 1 more Smart Citation
“…The determined values of the stress drop are listed in Table 3, they are in the range from 1.17 to 778.3 bar. Pandey et al, 2001 have been reported such high values of the stress drop for Chamoli earthquake, India.…”
Section: Stress Drop (Dd)mentioning
confidence: 92%
“…Brune (1970) has given a model to calculate the source parameters using near and far field displacement amplitude spectrum as a function of the physical parameters at the source. Abercombie and Leary (1993), Zoben and Hasakov (1995) and several others are notable recent contributors in the field of source parameters studies (Pandey et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The study was conducted in seismic zone III, and it was discovered that while ribbed slab structures have fewer columns than typical slab buildings, they perform less well in high seismic zones. However, this performance can be enhanced with structural retrofitting [8]. Pavan Kumar Jogi, Durga Chaitanya Kumar Jagarapu, and CH.…”
Section: Chamoli Earthquakementioning
confidence: 99%
“…Uttarakhand state falls in Zone IV (High Risk) and Zone V (Very High Risk) of the Bureau of Indian Standards' earthquake zonation map (Indian Standard, 2002), thus making it vulnerable to seismic hazards. The extensive damage to human life and property in Uttarakhand caused by the Uttarkashi and Chamoli earthquakes, underlined the ramifications of failing to incorporate seismic vulnerability in Master Plan formulation (Pandey et al 2001). Additionally, it is more challenging to reduce seismic vulnerability, in existing urban areas where already concentration of built-up and people has taken place.…”
Section: Introductionmentioning
confidence: 99%